The parental effect on educational and accupational attainment in Slovenia during the 20th century - Ganzeboom, Harry B.G. (Družboslovne razprave, 2000)
This paper empirically addresses social change and stability in Slovenia in the 20th century. After describing historical determinants and examining stratification research in Slovenia, it brings together information on long-term trends in intergenerational mobility, using the core of the Blau-Duncan model for estimating basic parental effect within occupational and educational attainment. The data, collected in a pooled data set, is representative of adults, aged from 21 to 64 years. They come from two different sources: firstly, from five (two-stage stratified) random samples of regular cross-section surveys, completed in 1968, 1973, 1980, 1989, and 1998(Slovenian Public Opinion Poll, i.e. SPOP), and, secondly, from three other random sample surveys, namely, from the Time Use Survey (1967), the Social Justice Project (1991), and the ISSP Survey (1992). The research designallows for cohort analysis, embracing labour market entry years of respondents from around 1920 to 1998. By using standard scales and methods the issues tend to be internationally comparable. The findings support the IMS hypothesis, namely, the existence of a significant negative linear trend in the parental effect over time. Surprisingly, the findings of a more detailed time analysis also expose a rather drastic decrease of parental effect during socialism in comparison to other CEE countries, followed by a sudden increase after the end of socialism (1990). The significant variations in parental effect over time are mainly the results of structural mobility factors, especially of a stronger political intervention on the educational system (to a higher extent) and labour markets (to a lesser extent) during socialism. Thereturn of a higher parental effect after the end of socialism, characterised by a more open economy, suggests that the former destratification policy could have been rather just (with more equal access topublic services like education and employment), but economically less-efficient.
Keywords: Slovenia; Slovenija; družbena diferenciacija; education; izobraževanje; družbena mobilnost; delovna mesta; zaposlovanje; 20.st.